Three‐dimensional heart locator for whole‐heart coronary magnetic resonance angiography. Issue 6 (22nd July 2013) - Moghari, Mehdi H.; Roujol, Sébastien; Henningsson, Markus; Kissinger, Kraig V.; Annese, David; Nezafat, Reza; Manning, Warren J.; Geva, Tal; Powell, Andrew J.
<x xml:space="preserve">Abstract</x> Purpose Coronary magnetic resonance angiography (MRA) is commonly performed with diaphragmatic navigator (NAV) gating to compensate for respiratory motion, but this approach is inefficient as data must be reacquired when it is outside the acceptance window. We therefore developed and validated a motion compensation technique based on three‐dimensional (3D) spatial registration in which data are accepted throughout the respiratory cycle. Methods A novel respiratory motion compensation method was implemented that acquires a low‐resolution 3D‐image of the heart (3D‐LOC) just prior to coronary MRA data acquisition. 3D‐LOC volumes were registered to the first 3D‐LOC to estimate the respiratory‐induced heart motion and to modify the coronary MRA data and reconstruct motion‐corrected images. Whole‐heart coronary MRA datasets were acquired from nine healthy subjects using a diaphragmatic NAV and using 3D‐LOC. Results There was no significant difference between the subjective image score of NAV and 3D‐LOC in three main coronary branches. The vessel sharpness of 3D‐LOC was higher than NAV in the right (0.44 ± 0.08 vs. 0.49 ± 0.08; P = 0.055) and left circumflex arteries (0.49 ± 0.05 vs. 0.52 ± 0.04; P = 0.039). Scan time for 3D‐LOC was significantly shorter than NAV (4.3 ± 0.6 vs. 8.3 ± 2.3 min; P = 0.004). Conclusion Compared to NAV gating, 3D‐LOC for coronary MRA reduces scan time by nearly 50% without compromising image quality. Magn Reson Med 71:2118–2126, 2014. © 2013 Wiley Periodicals, Inc.